Migrations et continentalisation en Guyane - Stéphane Granger (Territoire en Mouvement)
French Guiana, a French overseas territory, long lived in a near-complete ignorance of its geographical environment, because of its status, its exclusion from regional integration and the representations of its own inhabitants. However the numerous illicit flows integrating it informally to the continent, and more particularly the important border migrations, have brought the population and the political class, in the midst of a real identity quest since the 1960s, to grow closer to the Amazonian world. On the whole, to assume a new territoriality, of which the immigrants were the pioneers, and now exploited by France and the European Union for geopolitical and sustainable development stakes, which do not always coincide with the strategies of territorial affirmation of the Guianese people.